2020
DOI: 10.1038/s42003-020-01322-4
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde signaling by a mtDNA-encoded non-coding RNA preserves mitochondrial bioenergetics

Abstract: Alveolar epithelial type II (AETII) cells are important for lung epithelium maintenance and function. We demonstrate that AETII cells from mouse lungs exposed to cigarette smoke (CS) increase the levels of the mitochondria-encoded non-coding RNA, mito-RNA-805, generated by the control region of the mitochondrial genome. The protective effects of mito-ncR-805 are associated with positive regulation of mitochondrial energy metabolism, and respiration. Levels of mito-ncR-805 do not relate to steady-state transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 76 publications
3
35
0
Order By: Relevance
“…Our previous work demonstrated that the amount of mmu-mito-ncR-805 in the nucleus increased almost 10-fold in CSE-exposed cells. This increase coincided with the recovery from stress ( Blumental-Perry et al, 2020 ). An antisense inhibitor of mito-ncR-805, AI805, revealed a positive regulation of a subset of neMITO genes and energy metabolism by mito-ncR-805 ( Blumental-Perry et al, 2020 ).…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Our previous work demonstrated that the amount of mmu-mito-ncR-805 in the nucleus increased almost 10-fold in CSE-exposed cells. This increase coincided with the recovery from stress ( Blumental-Perry et al, 2020 ). An antisense inhibitor of mito-ncR-805, AI805, revealed a positive regulation of a subset of neMITO genes and energy metabolism by mito-ncR-805 ( Blumental-Perry et al, 2020 ).…”
Section: Resultsmentioning
confidence: 61%
“…This increase coincided with the recovery from stress ( Blumental-Perry et al, 2020 ). An antisense inhibitor of mito-ncR-805, AI805, revealed a positive regulation of a subset of neMITO genes and energy metabolism by mito-ncR-805 ( Blumental-Perry et al, 2020 ). Accordingly, overexpression of a synthetic oligo corresponding to the full-length mmu-mito-ncR-805 (mmu-ncR-805 FL ) increased the expression of a few neMITO genes and had a beneficial impact on the intermediates of the Krebs cycle ( Blumental-Perry et al, 2020 ).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Despite mitosRNAs exact biogenesis and cellular trafficking are still uncertain (Vendramin et al, 2017), many studies about their possible function were carried out. Of note, mito-ncR-805 has been shown to have a protective effect to cigarette smoke in alveolar epithelial cells, as well as an increased expression of nuclear-encoded genes important for mitochondrial function, supporting the idea that mitosRNAs regulation and function might be cell-type specific (Blumental-Perry et al, 2020).…”
Section: Retrograde Signalingmentioning
confidence: 78%